Aquaculture pond fertilazation : impacts of nutrient input on production - Mischke, Charles C. [ (Charles Christopher)] (Wiley-Blackwell, 2012)
"Aquaculture Pond Fertilization: Impacts of Nutrient Input on Production is a current, practical reference on the nutrient input techniques and strategies used to maximize production in freshwater pond culture systems. All fish raised in ponds require fertilizers to be added during certain developmental stages that differ from species to species. Pond culture systems are used across a wide variety of freshwater fish species and appropriate fertilization is an important component to raising robust, efficient fish. Fertilization regimens must factor in many variables ranging from location and water quality to species type, all of which can impact responses to fertilizer application. Aquaculture Pond Fertilization provides the reader with practical information on nutrient management and application from leading researchers in the field. Species specific chapters provide real world examples of fertilization strategies for such key species as catfish, bass, tilapia, perch, carp, sport fish, and ornamentals"-- Provided by publisher